1999
DOI: 10.2307/2648057
|View full text |Cite
|
Sign up to set email alerts
|

Migradollars and mortality: The effects of migration on infant survival in Mexico

Abstract: We apply multilevel methods to data from Mexico to examine how village migration patterns affect infant survival outcomes in origins. We argue that migration is a cumulative process with varying health effects at different stages of its progression, and test several related hypotheses. Findings suggest higher rates of infant mortality in communities experiencing intense U.S. migration. However, two factors diminish the disruptive effects of migration: migradollars, or migrant remittances to villages, and the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
141
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 188 publications
(153 citation statements)
references
References 20 publications
2
141
0
3
Order By: Relevance
“…Hamilton et al, 2009;Riosmena et al, 2013). On the other hand, studies have suggested that the impact of community outmigration may shift directions once migration becomes institutionalized, or normative, in a sending community (Kanaiaupuni and Donato, 1999). The null effects reported in other studies may capture heterogeneity in the impacts of community out-migration across communities with differing histories of migration; the net negative impact uncovered in our study may reflect the dominating influence of less institutionalized migration flows.…”
Section: Discussionmentioning
confidence: 47%
See 4 more Smart Citations
“…Hamilton et al, 2009;Riosmena et al, 2013). On the other hand, studies have suggested that the impact of community outmigration may shift directions once migration becomes institutionalized, or normative, in a sending community (Kanaiaupuni and Donato, 1999). The null effects reported in other studies may capture heterogeneity in the impacts of community out-migration across communities with differing histories of migration; the net negative impact uncovered in our study may reflect the dominating influence of less institutionalized migration flows.…”
Section: Discussionmentioning
confidence: 47%
“…Research focusing on infant health in Mexico has demonstrated that migration at both the household and community levels matters, but how migration matters depends on the dimension of migration studied. Specifically, this research finds that whereas remittances are beneficial for infant health, the absence of household and community members is harmful for infant health (Frank, 2005;Hamilton et al, 2009;Kanaiaupuni and Donato, 1999). This conclusion is based on studies focused on two highly related indicators of infant healthdLBW and infant mortality.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations